Legal Aspects of Municipal Service in Territory Development Programs. / Aspectos legales del Servicio municipal en programas de desarrollo territorial - Popadyuk, Nikita K.; Rozhdestvenskaya, Irina A.; Eremin, Sergey G.; Galkin, Andrey I.; Komov, Valery E. (Utopía y Praxis Latinoamericana)
ABSTRACT Municipal service in the Russian Federation has twenty years of existence. At the current stage of development of the Institute of municipal service, municipal employees are subjects of labor law, and the municipal service is one of the types of labor activity. However, the essence of the legal status of a municipal employee remains insufficiently studied. The proposed conclusions can contribute to the deepening of scientific developments in the field of labor law. The practical significance of the work is due to the relevance of the issues under consideration, the possibility of applying the proposed conclusions in practice. RESUMEN El Servicio municipal en la Federación de Rusia tiene veinte años de existencia. En la etapa actual de desarrollo del Instituto de servicios municipales, los empleados municipales son sujetos de derecho laboral, y el Servicio municipal es uno de los tipos de actividad laboral. Sin embargo, la esencia del estatuto jurídico de un empleado municipal se estudia insuficientemente. Las conclusiones propuestas pueden contribuir a la profundización de los avances científicos en el ámbito del derecho laboral. La importancia práctica del trabajo se debe a la pertinencia de las cuestiones que se examinan, la posibilidad de aplicar las conclusiones propuestas en la práctica.